BMCProtector: A Blockchain and Smart Contract Based Application for Music Copyright Protection - O'Mahony, Donal (My University, 2018)
n this paper, we explore the design and construct a prototype implementation of an Ethereum application, BMCProtector, which is based on Blockchain and Smart Contract technology, to protect music copyright and ensure rights holders income rights. With the blockchain, musicians can easily authorize and manage their music copyright on a public ledger. Without intermediaries being involved during the propagation process, rights holders can receive a greater share of royalty payments from the music industry automatically and instantly. We deal with piracy issues using encryption and watermarking methods. We also introduce a versioning mechanism to update the data in the smart contract for correcting mistakes made by the publisher. BMCProtector provides a solution to protect music copyright more effectively.
2018 International Conference on Blockchain Technology and Applications-ICBTA2018
PUBLISHED
Xi'an, China
Keywords: Blockchain; Smart contract; Copyright; Creative Technologies; Telecommunications; Bitcoin; Blockchain; Cryptography; Encryption